Relationship of left ventricular thrombus formation and adverse outcomes in acute anterior myocardial infarction in patients treated with primary percutaneous coronary intervention. Issue 1 (30th November 2018) - Zhang, Qian; Wang, Chun‐Mei; Shi, Shu‐Tian; Chen, Hong; Zhou, Yu‐Jie
Abstract : Background: The incidence of left ventricular thrombus (LVT) is 4% to 15% in patients with anterior acute ST‐segment elevation myocardial infarction (ant‐AMI) in the era of primary percutaneous coronary intervention (PPCI). And patients with LVT have higher in‐hospital mortality. Hypothesis: There is a relationship between LVT formation and 1‐year major adverse cardio‐cerebrovascular events (MACCE) in patients with ant‐AMI treated by PPCI. Methods: Our study population included 1488 consecutive patients with ant‐AMI. The primary endpoint was the incidence of MACCE within 1 year after AMI. The secondary endpoint was the thrombosis disappearance. Results: A total of 106 (7.1%) patients were diagnosed with LVT and 1382 (92.9%) patients without LVT. Patients with LVT had a higher incidence of MACCE than in patients without LVT (21.7%vs10.3%; P < 0.001). Univariate analysis showed LVT was associated with an increase in MACCE risk (odds ratio [OR] = 2.40; 95% confidence interval [CI] [1.37‐4.21]; P < 0.001). When examining MACCE components individually, LVT was only associated with the incidence of congestive heart failure (OR = 2.41; 95% CI [1.29‐4.58]; P = 0.001). After adjustment for principal confounders, LVT remained an independent risk factor for MACCE (HR = 2.28; 95% CI [1.12‐6.38]; P = 0.020). Other independent predictors include 24‐hour LVEF, creatine kinase peak value, and age. Further analysis found patients with LVT in international normalized ratio (INR) ≥ 2 group had lower MACCE risk and higher thrombus disappearance than in INR < 2 group (13.5%vs29.6%; P = 0.044; 90.4%vs74.1%; P = 0.029). Conclusion: For patients with ant‐AMI treated by PPCI, LVT is an independent predictor of 1‐year MACCE events. Treatment with vitamin K antagonist in the therapeutic range (INR ≥ 2) has the potential to reduce MACCE risk and promote disappearance of thrombus.